Analysis of School Health Unit Program Practices with Clean and Healthy Living Behavior - Sidiq, Fahmi; Hidayana, Rizki Apriva; Amal, Moh Alfi (International Journal of Health, Medicine, and Sports, 2024)
This research aims to explore the relationship between knowledge, availability of infrastructure, and the role of teachers and clean and healthy living behavior (PHBS) among students in the school environment during the Covid-19 pandemic. The research method uses a quantitative approach with a Cross Sectional design and is carried out on students from State Elementary Schools (SDN). Data was collected through questionnaires and documentation, then analyzed using Univariate Analysis and Bivariate Analysis. The results of the research show that there is a significant relationship between student knowledge, availability of infrastructure, and the role of teachers with clean and healthy living behavior in the school environment. These factors play an important role in forming students' awareness and compliance with health protocols during the Covid-19 pandemic. This research makes an important contribution to efforts to ensure the safety and health of students in the school environment in the midst of a pandemic and emphasizes the importance of health education and the implementation of PHBS.